Long-Term Dynamics of the Thermal State of Technogenic Plots in Siberia Based on Satellite Data - Tatiana Ponomareva; Nikita Yakimov; Georgy Ponomarev; Evgenii Ponomarev (Environmental Sciences Proceedings, 2022)
We studied the dynamics of relative anomalies (ΔT/Tbg) in the ground cover thermal regime of technogenic territories in Siberia under the conditions of gold mining impact. The impact of gold deposit mining determines the change in the thermal state of the post-technogenic plots for a long time, which is an important feature of ecosystem stability monitoring. We analyzed the spectral characteristics of four technogenic sites that had gold mining quarries of different age. We evaluated the stages of technogenic plots according to the initial level of thermal anomaly, the rate of decrease in thermal anomaly, the time of stabilization recovery processes, and dispersing of the residual level of thermal anomaly.